The Influence of Scout Activities on Elementary School Students' Attitudes in Leadership and Independence Aspects. - Septian, Fadillah; Yuliyanto, Aan; Affandi, Ahmad; Irawan; Nurkhofifah, Siti (International Conference on Elementary Education, 2024)
A teacher-centered learning process, where educators consider themselves a store of knowledge, is no longer relevant. Baden Powell has shifted the learning process to be student-centered (ask the boys-students centered) through Scouting activities. This literature review aims to determine the influence of scouting activities on students' leadership character and independence. Scouts have eight methods for carrying out their activities, including an honor code, learning to do, a group system, interesting, challenging, in the open, in the presence of adults, signs of proficiency, and separate units. One way to achieve leadership and independence is belief in one's abilities; this can be achieved through learning by doing activities, and this is the application of the scouting method. In this way, this literature review can be a reference for improving students' leadership character and independence through scouting extracurricular activities that apply scouting methods correctly and additionally apply the among system correctly. Thus, through a holistic approach involving education, independence, and extracurricular activities such as scouting, it is hoped that students can develop strong and positive leadership attitudes. The weakness of this research is that success will not be achieved if a researcher does not have Scouting skills or, in this case, does not have a Basic Advanced Course (KMD). This can happen because the researcher does not understand the existing context.